Revisiting Treatment Strategies: Addressing Epithelial-to-Mesenchymal Transition-Induced Resistance in Hepatocellular Carcinoma - Roghayeh Naserkhaki; Bahare Shokouhian; Yaser Tahamtani; Arezoo Khosravi; Siavash Iravani; Ali Zarrabi; Massoud Vosough (BME Frontiers, 2025)
One of the major therapeutic challenges for hepatocellular carcinoma (HCC), the most form of primary liver cancer, is how to overcome drug resistance. Due to the high failure rate of systemic therapy in treating advanced HCC patients and the increasing recurrence rate, HCC is a highly lethal malignancy. Primary and acquired drug resistance are major contributing factors to the patients with advanced HCC who do not respond effectively to long-term systemic therapy. Therefore, it is essential to look into the molecular processes that lead to drug resistance. Different studies have indicated that epithelial-to-mesenchymal transition (EMT) plays a critical part in the emergence of drug resistance. Several signaling pathways regulate this phenomenon. This review primarily concentrates on drug resistance triggered by EMT, especially in the context of HCC. The key signaling pathways that cause drug resistance in HCC, including transforming growth factor-β and epidermal growth factor receptor signaling, liver cancer stem cells, and noncoding RNAs, are highlighted in the present study, along with the most recent molecular targets discovered to prevent drug resistance. These targets could help develop novel and combinatory HCC therapy approaches. Therefore, this review aims to provide both the latest findings on molecular basis and potential solutions for HCC drug resistance.